Kinesio taping in treatment and prevention of sports injuries: A meta-analysis of the evidence for its effectiveness - Williams, S.; Whatman, C.; Hume, P. A.; Sheerin, K. (Sports Medicine, 2012)
Kinesio tape (KT) is an elastic therapeutic tape used for treating sports injuries and a variety of other disorders. Chiropractor, Dr Kenso Kase, developed KT taping techniques in the 1970s. It is claimed that KT supports injured muscles and joints and helps relieve pain by lifting the skin and allowing improved blood and lymph flow. The profile of KT rose after the tape was donated to 58 countries for use during the 2008 Olympic Games, and was seen on high-profile athletes. Practitioners are asking whether they should use KT over other elastic adhesive tapes. The aim of this review was to evaluate, using meta-analysis, the effectiveness of KT in the treatment and prevention of sports injuries. Electronic databases including SPORTDiscus™, Scopus, MEDLINE, ScienceDirect and sports medicine websites were searched using keywords `kinesio taping/tape`. From 97 articles, ten met the inclusion criteria (article reported data for effect of KT on a musculoskeletal outcome and had a control group) and were retained for meta-analyses. Magnitude-based inferences were used to assess clinical worth of positive outcomes reported in studies. Only two studies investigated sports-related injuries (shoulder impingement), and just one of these involved injured athletes. Studies attending to musculoskeletal outcomes in healthy participants were included on the basis that these outcomes may have implications for the prevention of sporting injuries. The efficacy of KT in pain relief was trivial given there were no clinically important results. There were inconsistent range-of-motion outcome results, with at least small beneficial results seen in two studies, but trivial results in two other studies across numerous joint measurements. There was a likely beneficial effect for proprioception regarding grip force sense error, but no positive outcome for ankle proprioception. Seven outcomes relating to strength were beneficial, although there were numerous trivial findings for quadriceps and hamstrings peak torque, and grip strength measures. KT had some substantial effects on muscle activity, but it was unclear whether these changes were beneficial or harmful. In conclusion, there was little quality evidence to support the use of KT over other types of elastic taping in the management or prevention of sports injuries. KT may have a small beneficial role in improving strength, range of motion in certain injured cohorts and force sense error compared with other tapes, but further studies are needed to confirm these findings. The amount of case study and anecdotal support for KT warrants well designed experimental research, particularly pertaining to sporting injuries, so that practitioners can be confident that KT is beneficial for their athletes.